MORPHO-CONSERVATION ANALYSIS IN CRITICAL HILLS OF BINUANG MICRO-WATERSHED, SOUTH KALIMANTAN - Ayuningtyas, Efrinda Ari; Khasanah, Alfiatun Nur (Bulletin of Scientific Contribution, 2024)
Geomorphology is crucial in analyzing erosion potential and selecting conservation measures to improve land resources. Morphometric analysis reveals that the Binuang Micro Watershed, with its upper part being a critical hilly area, has a high erosion potential due to the occurrence of splash erosion, sheet erosion, and rill erosion in all existing landforms. The analysis of watershed morphometry, such as shape, area, drainage density, bifurcation ratio, and drainage density, using DEM data at the research site, reveals a strong correlation between the morphometric conditions of the Binuang Micro Watershed and the incidence of erosion and flood inundation. These conditions are also influenced by the dominant soil texture, namely clay. This research has developed recommendations for conservation actions based on morphometry and the level of erosion occurrence for each landform condition. These recommendations are intended for policymakers to prioritize natural resource management for the sustainability of watershed development.